Salivary and Serum Interleukin-10, C-Reactive Protein, Mean Platelet Volume, and CRP/MPV Ratio in the Diagnosis of Late-Onset Neonatal Sepsis in Full-Term Neonates - Ahmed Omran; Hazem Sobh; Mohamed Osama Abdalla; Sonya El-Sharkawy; Ahmed R. Rezk; Abdelmoneim Khashana (Journal of Immunology Research)
Salivary markers could serve as potential noninvasive markers in the diagnosis of neonatal infections. We aimed to investigate the diagnostic role of salivary and serum interleukin 10 (IL-10), C-reactive protein (CRP), mean platelet volume (MPV), and CRP/MPV ratio in the diagnosis of late-onset neonatal sepsis in full-term neonates. Seventy full-term neonates were enrolled in this prospective case-control study, 35 with late-onset neonatal sepsis, and 35 controls. Salivary IL-10, serum IL-10, and CRP concentrations were measured by enzyme-linked immunosorbent assay (ELISA). Complete blood (CBC) count was measured by an automated blood cell counter. The salivary IL-10, serum IL-10, CRP, MPV, and CRP/MPV ratio levels were much higher in neonates with late-onset sepsis than in control (220±150 vs. 18±9 pg/ml, P<0.001), (316±198 vs. 23.7±14 pg/ml, P<0.001), (78.2±34 vs. 3.3±1.7 mg/L, P<0.001), (11.2±0.9 vs. 8.6±0.4 fL), and (7.08±3.3 vs. 0.4±0.2, P<0.001), respectively. At the cutoff point of >31 pg/ml, salivary IL-10 showed 97.1% sensitivity and 94.3% specificity. Serum IL-10 at a cutoff value of ≥33.6 pg/ml had a sensitivity of 97.1% and specificity of 80%. MPV showed a sensitivity of 100% and specificity of 94.4% at a cutoff value≥9.2 fL. CRP/MPV ratio showed a sensitivity of 100% and specificity of 97.1% at a cutoff value>0.9. Salivary and serum IL-10 showed a positive correlation with CRP and CRP/MPV ratio in septic neonates. The current study shows for the first time that both salivary IL-10 and CRP/MPV showed statistically significant differences between neonates with late-onset sepsis and controls. Accordingly, salivary IL-10 could serve as a potential noninvasive biomarker for the diagnosis of late-onset sepsis in full-term neonates.